Cholesterol metabolites exported from human brain - Yuqin Wang (Steroids, 2015)
The human brain contains approximately 25% of the body's cholesterol. The brain is separated from the circulation by the blood brain barrier. While cholesterol will not passes this barrier, oxygenated forms of cholesterol can cross the barrier. Here by measuring the difference in the oxysterol content of blood plasma in the jugular vein and in a forearm vein by mass spectrometry (MS) we were able to determine the flux of more than 20 cholesterol metabolites between brain and the circulation. We confirm that 24S-hydroxycholesterol is exported from brain at a rate of about 2 - 3 mg/24 hr. Gas chromatography (GC) - MS data shows that the cholesterol metabolites 5α-hydroxy-6-oxocholesterol (3β,5α-dihydroxycholestan-6-one), 7β-hydroxycholesterol and 7-oxocholesterol, generally considered to be formed through reactive oxygen species, are similarly exported from brain at rates of about 0.1, 2 and 2 mg/24 hr, respectively. Although not to statistical significance both GC-MS and liquid chromatography (LC) - MS methods indicate that (25R)26-hydroxycholesterol is imported to brain, while LC-MS indicates that 7α-hydroxy-3-oxocholest-4-enoic acid is exported from brain.